Analisis Komparatif Metode Pemahaman Hadis Ulama Kontemporer: Studi Teori Yusuf Al-Qaradhawy - Zulkifli Abdurrahman Usman; Achievinna Mirza Senathalia (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2021)
This article discusses the method of understanding hadith in the view of contemporary scholars. The focus of this article is to reveal and analyze the theory of the hadith understanding method proposed by Yusuf al-Qardhawy. The analysis of this article uses a qualitative method with an approach to the science of hadith, history, and comparative analysis. The findings of this study show that the theory of the method of understanding Yusuf al-Qaradhawy's hadith is very fundamental in an effort to understand the hadiths of the prophet. The theory is something that is integral and therefore cannot be simply rejected. Comparative analysis with other contemporary scholars such as Muhammad al-Ghazali, Mustafa Yakkub, al-Albani, and Hasbi Ash-Shiddiqi shows the uniqueness and significance of Yusuf al-Qaradhawy's theory which is inherent, fundamental, and comprehensive.